A silicon films deposition in the process of SIF 4 decomposition in pulsed glow discharge; Известия вузовй. Физика; Vol. 55, № 12-3 - Shugurov V. V. Vladimir Viktorovich; Denisov V. V.; Kalushevich A. A.; Yakovlev V. V.; Vorobjev (Vorobyov) M. S. Maksim Sergeevich; Suslov A. I.; Koval N. N. Nikolay Nikolaevich (2012, 2012)
Title screen